The house of Wolves [large type] - Patterson, James, 1947-; Lupica, Mike (Patterson, James, 1947- House of Wolves, 2023)
The Wolfs, the most powerful family in California, have a new head-thirty-six-year-old former high school teacher Jenny Wolf. That means Jenny now runs the prestigious San Francisco Tribune. She also controls the legendary pro football team, the Wolves. And she hopes to solve her father's murder.